2023
DOI: 10.1029/2022ja030779
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Chorus Wave Excitation in the Compressed/Stretched Dipole Magnetic Field

Abstract: Whistler mode chorus waves are strong electromagnetic emissions frequently observed in the Earth's magnetosphere. They can appear as rising tones, falling tones, and hiss-like emissions in dynamic spectra (Gao et al., 2014;Li et al., 2012). In general, the chorus waves with distinct elements are repetitive Lu et al., 2021;Shue et al., 2015). There is usually a power gap around 0.5 ๐ด๐ด ๐ด๐ด๐‘๐‘๐‘๐‘ (where ๐ด๐ด ๐ด๐ด๐‘๐‘๐‘๐‘ is the electron gyrofrequency at the equator), naturally forming lower (0.1-0.5 ๐ด๐ด ๐ด๏ฟฝ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In addition, the compressional ULF waves can also modulate chorus waves by changing magnetic field gradient (Li et al., 2022). Simulation results have clearly shown that the change of the inhomogeneity or curvature of background magnetic field can affect the fine structure of chorus waves (Katoh & Omura, 2013; Kong et al., 2023). Although several studies have reported the appearance and quench of chorus waves caused by the solar wind dynamic pressure (Fu et al., 2012; Liu et al., 2017; Yue et al., 2017; Zhou et al., 2015), there is still no direct observation on the modulation of fine structures of chorus waves by solar wind dynamic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the compressional ULF waves can also modulate chorus waves by changing magnetic field gradient (Li et al., 2022). Simulation results have clearly shown that the change of the inhomogeneity or curvature of background magnetic field can affect the fine structure of chorus waves (Katoh & Omura, 2013; Kong et al., 2023). Although several studies have reported the appearance and quench of chorus waves caused by the solar wind dynamic pressure (Fu et al., 2012; Liu et al., 2017; Yue et al., 2017; Zhou et al., 2015), there is still no direct observation on the modulation of fine structures of chorus waves by solar wind dynamic pressure.…”
Section: Introductionmentioning
confidence: 99%